Post-Soviet Central Asian States’ Policies towards the Treaty on the Prohibition of Nuclear Weapons - K. G. Muratshina (Управленческое консультирование)
The Treaty on the Prohibition of Nuclear Weapons (TPNW) was introduced in the United Nations’ agenda in 2017. Since then, it remains a corner stone in the discussions on the perspectives of the non-proliferation of weapons of mass destruction. The Treaty has already divided the community of non-nuclear states and stipulated the rise of anti-nuclear activism around the world. This paper is aimed at the analysis of the position of post-Soviet Central Asian states towards TPNW. The author consequently analyses the reaction of the governments of Kazakhstan, Tajikistan, Uzbekistan, Kyrgyzstan and Turkmenistan, with the special focus on Kazakhstan’s policy, as this country supports TPNW and demonstrates an example of the most consistent anti-nuclear policy course. The review of the Central Asian states’ positions towards TPNW is worth studying in particular due to their partnership with Russia, and the specific feature of combining the partnership and sometimes different views on the international issues.